Aminoguanidine oxalate second-order nonlinear optical crystal material as well as preparation and application thereof

By developing second-order nonlinear optical crystal materials of aminoguanidine oxalate with symmetrically incomplete planar functional motifs, the problem of limitation of optical performance of existing commercial frequency multiplier crystals is solved, and a strong frequency multiplier effect and moderate birefringence are achieved, showing application potential in the field of nonlinear optical.

CN119753848AActive Publication Date: 2025-04-04TONGJI UNIV

Patent Information

Application Number
CN202411989321.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-04
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

The application of existing commercial frequency multiplier crystals in cutting-edge fields is limited by their own optical properties, which is difficult to meet the growing production and scientific research needs.

Method used

A second-order nonlinear optical crystal material of aminoguanidine oxalate has a plane functional primitive with symmetry, breaking the microscopic symmetry of traditional planar triangle primitives and having large microscopic polarization and polarization anisotropy.

Benefits of technology

The crystal material exhibits strong powder frequency doubling effect, suitable birefringence and short UV absorption cut-off edges, achieving the optical performance index of commercial frequency doubling crystals and showing broad application potential in the field of nonlinear optics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119753848A_ABST
    Figure CN119753848A_ABST
Patent Text Reader

Abstract

The invention relates to an aminoguanidine oxalate second-order nonlinear optical crystal material and preparation and application thereof, the chemical formula of the crystal material is (CN4H7) + (C2O4H)-, the crystal material belongs to a monoclinic system, the space group is P21, the cell parameters are # imgabs0 # and # imgabs1 #, alpha is equal to 90 degrees, beta is equal to 95-100 degrees, gamma is equal to 90 degrees, and Z is equal to 2. The powder frequency-doubled effect of the nonlinear optical crystal (CN4H7) + (C2O4H)-disclosed by the invention under the irradiation of 1064nm laser is about 1.0 time of that of a KH2PO4 (KDP) crystal, and phase matching can be realized. In addition, the crystal material has the advantages of being short in ultraviolet absorption cut-off edge (290 nm), easy to grow and the like, and has important application value in the photoelectric conversion fields of stereolithography, solid-state lasers, optical communication, optical parametric amplifiers, optical parametric oscillators, laser frequency converters and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nonlinear optical crystalline materials, and relates to an aminoguanidine oxalate second-order nonlinear optical crystal material and a preparation method and application thereof. Background Art

[0002] As an important optoelectronic functional material, nonlinear optical (NLO) crystalline materials are widely used in laser frequency conversion, optical communication, optoelectronic modulation, 3D printing, stereolithography, national defense and military and other fields. With the continuous development of society and the expansion of application fields, the existing commercial frequency doubling crystals can no longer meet the growing production and scientific research needs. Therefore, the research and development of new NLO materials with better performance and suitable for different wavelength ranges has become an important task and challenge faced by modern scientific researchers. At present, the use of π-conjugated planar structural units (such as [BO3] 3- , [CO3] 2- , [NO3] - )Developing new NLO materials is an effective strategy. For example, LiB3O5(LBO), CsB3O5(CBO), CsLiB6O 10 (CLBO), β-BaB2O4 (BBO) and KBe2BO3F2 (KBBF) crystals are all based on this type of structural unit. However, the inherent optical performance shortcomings of these materials limit their application in cutting-edge fields. Therefore, the development of new high-performance NLO crystalline materials is an important research direction in the field of optoelectronic functional materials. Summary of the invention

[0003] The purpose of the present invention is to provide an aminoguanidine oxalate second-order nonlinear optical crystal material and its preparation and application. The crystalline material has a symmetry-incomplete planar functional unit (CN4H7) + This unit breaks the microscopic symmetry of the traditional planar triangle unit and has a large microscopic polarizability and polarizability anisotropy. The crystalline material exhibits a strong powder frequency-doubling effect (1.0×KDP@1064nm), a suitable birefringence (0.016@546nm) and a short ultraviolet absorption cutoff edge (290nm).

[0004] The purpose of the present invention can be achieved by the following technical solutions:

[0005] In a first aspect, the present invention provides an aminoguanidine oxalate second-order nonlinear optical crystal material, the chemical formula of which is (CN4H7) + (C2O4H) - , belongs to the monoclinic system, the space group is P21, and the unit cell parameters are α=90°, β=95~100°, γ=90°, Z=2.

[0006] Furthermore, the unit cell parameters of the crystal material are α=90°,β=96~98°,γ=90°,Z=2. Further preferably, the unit cell parameters are α=90°,β=97~98°,γ=90°,Z=2. Most preferably, the unit cell parameters are α=90°, β=97.814(4)°, γ=90°, Z=2.

[0007] In the second aspect, the present invention provides a method for preparing an aminoguanidine oxalate second-order nonlinear optical crystal material, comprising mixing an aminoguanidine source, an oxalic acid source and a solvent, adding them to a reaction vessel and stirring, heating the reaction, cooling to room temperature, and obtaining colorless and transparent block crystals by volatilizing the solvent, which are the target product.

[0008] Furthermore, the molar ratio of the aminoguanidine source to the oxalic acid source is (1-10):(1-10).

[0009] Furthermore, the aminoguanidine source is selected from at least one of aminoguanidine bicarbonate, aminoguanidine sulfate or aminoguanidine hydrochloride.

[0010] Furthermore, the oxalic acid source is selected from at least one of anhydrous oxalic acid, oxalic acid dihydrate or sodium oxalate.

[0011] Furthermore, the heating reaction temperature is 30-60°C and the time is not less than 10 minutes.

[0012] Furthermore, the solvent is distilled water.

[0013] Aminoguanidine oxalate (CN4H7) of the present invention + (C2O4H) - The crystal structure of Figure 1 The protonated aminoguanidine cation reacts with the deprotonated hydrogen oxalate anion via N–H … O hydrogen bonds form a network structure.

[0014] In a third aspect, the present invention provides an application of an aminoguanidine oxalate second-order nonlinear optical crystal material in stereolithography, solid-state lasers, optical communications, optical parametric amplifiers, optical parametric oscillators, and laser frequency converters.

[0015] Furthermore, the crystal material is used in a laser frequency converter and outputs 532nm laser under 1064nm laser irradiation. Its powder frequency doubling intensity is 1.0 times that of KDP crystal and can achieve phase matching.

[0016] The present invention combines a symmetry-incomplete planar cation with a π-conjugated anion to invent an aminoguanidine oxalate second-order nonlinear optical crystal (CN4H7) + (C2O4H) - The crystalline material has a symmetry-incomplete planar structural unit, which is conducive to the generation of large microscopic polarizability and polarizability anisotropy. The crystalline material exhibits a strong powder frequency-doubled effect (1.0×KDP@1064nm), a moderate birefringence (0.016@546nm) and a short ultraviolet absorption cutoff edge (290nm).

[0017] Compared with the prior art, the present invention has the following advantages:

[0018] (1) This application provides a new second-order nonlinear optical crystal (CN4H7) + (C2O4H) - The crystalline material has a strong frequency doubling effect. Under 1064nm laser irradiation, the frequency doubling intensity is 1.0 times that of the commercial frequency doubling crystal KDP, and phase matching can be achieved. In addition, the ultraviolet absorption cutoff edge of the crystalline material is 290nm, and the birefringence is 0.016@546nm. The crystalline material has reached the optical performance indicators of commercial frequency doubling crystals, showing broad application potential in the field of nonlinear optics.

[0019] (2) The present application also provides the second-order nonlinear optical crystal (CN4H7) + (C2O4H) - The preparation method uses solvent evaporation method to prepare colorless and transparent block (CN4H7) + (C2O4H) - The synthesis method is simple, the synthesis conditions are mild, it is easy to obtain high-purity millimeter-level single crystals, and it is easy to prepare in large quantities. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 Yes (CN4H7) + (C2O4H) - Schematic diagram of the crystal structure;

[0021] Figure 2 The X-ray diffraction pattern of sample 1-1# obtained by fitting the crystal structure analyzed by single crystal X-ray diffraction is compared with the pattern obtained by X-ray diffraction test after sample 1-1# is ground into powder;

[0022] Figure 3 is the UV-visible absorption spectrum of sample 1-1#;

[0023] Figure 4is the infrared spectrum of sample 1-1#;

[0024] Figure 5 This is the second harmonic phase matching diagram of sample 1-1# in the 1064nm band;

[0025] Figure 6 It is the second harmonic signal diagram of sample 1-1# and standard KDP sample with sample size ranging from 150 to 200 μm. DETAILED DESCRIPTION

[0026] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.

[0027] In the following examples, unless otherwise specified, raw materials or processing techniques are conventional commercially available raw materials or conventional processing techniques in the art.

[0028] Embodiment 1:

[0029] Preparation of samples 1# to 8#

[0030] The aminoguanidine source (i.e. (CN4H7) + HCO3, aminoguanidine bicarbonate), oxalic acid source (i.e. anhydrous oxalic acid), and solvent are mixed and added to a beaker. The beaker is placed on a constant temperature magnetic heating table, heated and stirred until a clear and transparent solution is obtained, and then cooled to room temperature. By slowly evaporating the solvent, a colorless and transparent block crystal (CN4H7) can be obtained. + (C2O4H) - .

[0031] The relationship between the type and ratio of raw materials in the initial mixture, heating temperature, stirring time and sample number is shown in Table 1.

[0032] Table 1 Correspondence between samples, raw materials and synthesis conditions

[0033]

[0034] Crystal structure analysis of samples 1-1# to 1-8#

[0035] The structures of samples 1-1# to 1-8# were analyzed using single crystal X-ray diffraction and powder X-ray diffraction methods.

[0036] The single crystal X-ray diffraction test was carried out on a D8 VENTURE CMOS X-ray single crystal diffractometer from Bruker, Germany. The data collection temperature was 298.15K, and the diffraction light source was graphite monochromatized Mo-Kα rays. The scanning mode was ω; the data were processed for absorption correction using the Multi-Scan method. The structure analysis was completed using the SHELXTL-2018 program package; the positions of heavy atoms were determined using the direct method, and the coordinates of the remaining atoms were obtained using the difference Fourier synthesis method; the F-based 2 The full-matrix least-squares method was used to refine the coordinates of all atoms and the anisotropic thermal parameters.

[0037] The powder X-ray diffraction test was carried out on a Bruker D8 X-ray powder diffractometer from Bruker, Germany. The test conditions were a fixed target monochromatic light source Cu Kα, a wavelength of The voltage and current are 40 kV / 20 A, the slits DivSlit / RecSlit / SctSlit are 2.00 deg / 0.3 mm / 2.00 deg respectively, the scanning range is 5 to 70°, and the scanning step is 0.02°.

[0038] Among them, the single crystal X-ray diffraction results show that samples 1-1# to 1-8# have the same chemical formula and crystal structure, and the chemical formula is (CN4H7) + (C2O4H) - , which belongs to the monoclinic system, the space group is P21, and the unit cell parameters are α=90°, β=97.8~97.9°, γ=90°, Z=2;

[0039] Take sample 1-1# as a typical representative, its crystal structure data is α=90°,β=97.814(4)°,γ=90°,Z=2. Its crystal structure is as follows Figure 1 shown.

[0040] The powder X-ray diffraction test results show that in the XRD spectra of samples 1-1# to 1-8#, the positions of the diffraction peaks of the samples and the diffraction peaks fitted by the single crystal data are the same, but the peak intensities are slightly different.

[0041] Take sample 1-1# as a typical example. Figure 2 As shown, the X-ray diffraction pattern obtained by fitting the crystal structure analyzed by single crystal X-ray diffraction is consistent with the peak position of the pattern obtained by X-ray diffraction test after sample 1-1# is ground into powder, indicating that the obtained sample has high purity.

[0042] UV-Visible absorption spectrum test

[0043] The diffuse reflectance absorption spectrum test of sample 1-1# was conducted on a Carry 5000 UV-visible-near infrared spectrophotometer from Agilent Technologies, USA. Figure 3 As shown by Figure 3It can be seen that the ultraviolet absorption cutoff edge of this compound is 290nm.

[0044] Infrared spectrum test

[0045] The infrared spectrum test of sample 1-1# was conducted on a Nicolet iS10 Fourier infrared spectrometer from Thermo Fisher Scientific Inc., USA. The results are as follows Figure 4 As shown in the infrared spectrum, 3187, 3348 and 3451 cm -1 The characteristic absorption peak at confirms that [CN4H7] + The presence of groups.

[0046] Frequency doubling test experiment and results

[0047] The frequency doubling test experiment of sample 1-1# is as follows: a laser with a wavelength of 1064nm generated by a Q-switched Nd:YAG solid laser is used as the fundamental frequency light to irradiate the tested crystal powder, a spectrometer is used to detect the generated second harmonic, and an oscilloscope is used to display the harmonic intensity. The crystal sample and the standard sample KDP crystal are ground separately, and crystals of different particle sizes are sieved out with a standard sieve, with particle sizes ranging from 26 to 50, 50 to 74, 74 to 105, 105 to 150, and 150 to 200 μm, respectively. Observe the change law of the frequency doubling signal with the particle size to determine whether it can achieve phase matching. Under the same test conditions, compare the second harmonic intensity generated by the sample and the standard sample KDP to obtain the relative size of the sample frequency doubling effect.

[0048] The test results show that the compound (CN4H7) + (C2O4H) - It has a large powder frequency-doubled effect. Under 1064nm wavelength laser irradiation, the frequency-doubled signal intensity is 1.0 times that of KDP crystal (such as Figure 6 ). The crystalline material can achieve phase matching under 1064nm laser irradiation (such as Figure 5 ).

[0049] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. An aminoguanidine oxalate second-order nonlinear optical crystal material, characterized in that: Its chemical formula is (CN4H7) + (C2O4H) - , belongs to the monoclinic system, the space group is P21, and the unit cell parameters are α=90°, β=95~100°, γ=90°, Z=2.

2. The aminoguanidine oxalate second-order nonlinear optical crystal material according to claim 1, characterized in that: The unit cell parameters of the crystal material are α=90°, β=96~98°, γ=90°, Z=2.

3. The method for preparing the aminoguanidine oxalate second-order nonlinear optical crystal material according to claim 1 or 2, characterized in that: The aminoguanidine source, the oxalic acid source and the solvent are mixed, added into a reaction container and stirred, heated for reaction, cooled to room temperature, and the solvent is evaporated to obtain colorless and transparent block crystals, which are the target product.

4. The method for preparing the aminoguanidine oxalate second-order nonlinear optical crystal material according to claim 3, characterized in that: The molar ratio of the aminoguanidine source to the oxalic acid source is (1-10):(1-10).

5. The method for preparing the aminoguanidine oxalate second-order nonlinear optical crystal material according to claim 3, characterized in that: The aminoguanidine source is selected from at least one of aminoguanidine bicarbonate, aminoguanidine sulfate or aminoguanidine hydrochloride.

6. The method for preparing the aminoguanidine oxalate second-order nonlinear optical crystal material according to claim 3, characterized in that: The oxalic acid source is selected from at least one of anhydrous oxalic acid, oxalic acid dihydrate or sodium oxalate.

7. The method for preparing the aminoguanidine oxalate second-order nonlinear optical crystal material according to claim 3, characterized in that: The heating reaction temperature is 30-60°C and the time is not less than 10 minutes.

8. The method for preparing the aminoguanidine oxalate second-order nonlinear optical crystal material according to claim 3, characterized in that: The solvent is distilled water.

9. Application of the aminoguanidine oxalate second-order nonlinear optical crystal material as claimed in claim 1 or 2 in stereolithography, solid-state lasers, optical communications, optical parametric amplifiers, optical parametric oscillators, and laser frequency converters.

10. The use of the aminoguanidine oxalate second-order nonlinear optical crystal material according to claim 9, characterized in that: The crystal material is used in laser frequency converters and outputs 532nm laser under 1064nm laser irradiation.

Citation Information

Patent Citations

  • Guanidine phosphate ultraviolet frequency doubling crystal material, and preparation method and application thereof

    CN113322518A

  • Hydroxyl phosphorous acid aminoguanidine nonlinear optical crystal as well as preparation method and application thereof

    CN118996633A

  • 4-amino-1, 2, 4-triazole nitrate second-order nonlinear optical crystal material and preparation and application thereof

    CN119082870A

Cited By

  • Birefringent crystal material and preparation method and application thereof

    CN120210960A

  • Lithium 2-hydroxyethanesulfonate second-order nonlinear optical crystal and preparation and application thereof

    CN121496572A